Co‐occurring medical conditions in adults with Down syndrome: A systematic review toward the development of health care guidelines. Issue 1 (12th November 2017) - Capone, George T.; Chicoine, Brian; Bulova, Peter; Stephens, Mary; Hart, Sarah; Crissman, Blythe; Videlefsky, Andrea; Myers, Katherine; Roizen, Nancy; Esbensen, Anna; Peterson, Moya; Santoro, Stephanie; et al.
Abstract : Adults with Down syndrome (DS) represent a unique population who are in need of clinical guidelines to address their medical care. The United States Preventive Service Task Force (USPSTF) has developed criteria for prioritizing conditions of public health importance with the potential for providing screening recommendations to improve clinical care. The quality of existing evidence needed to inform clinical guidelines has not been previously reviewed. Using the National Library of Medicine (NLM) database PubMed, we first identified 18 peer reviewed articles that addressed co‐occurring medical conditions in adults with DS. Those conditions discussed in over half of the articles were prioritized for further review. Second, we performed detailed literature searches on these specific conditions. To inform the search strategy and review process a series of key questions were formulated a priori. The quality of available evidence was then graded and knowledge gaps were identified. The number of participating adults and the design of clinical studies varied by condition and were often inadequate for answering all of our key questions. We provide data on thyroid disease, cervical spine disease, hearing impairment, overweight‐obesity, sleep apnea, congenital heart disease, and osteopenia‐osteoporosis. Minimal evidence demonstrates massive gaps in our clinical knowledge that compromises clinical decision‐making and management of these medically complex individuals. The development of evidence‐based clinical guidance will require an expanded clinical knowledge‐base in order to move forward.